Analysis of The Effect of Work Stress and Work Environment on Employee Performance Arema Aremania Bersatu Berprestasi Indonesia Ltd. - Eirene Yonastasia Riyadi; Dwi Wulandari; Grisvia Agustin (Journal Research of Social Science, Economics, and Management, 2021)
One of the determinants of a company's progress, both service and non-service, is the resources it has. The company or a business entity feels that the company's goals will not be achieved without quality resources. However, they often do not realize that companies only make employees or their resources tools/assets to achieve company goals, not as individuals who need recognition and appreciation. This study aimed to analyze How much influence the work environment and work stress have on employee performance at Arema Aremania Bersatu Berprestasi Indonesia Ltd. In this study, the independent variables are Work Stress (X1) and Work Environment (X2), while the dependent variable is Employee Performance (Y). This type of research is quantitative research analyzed using statistics. The number of samples obtained by using a saturated sample that makes the entire population of Arema Aremania Bersatu Berprestasi Indonesia Ltd. became a sample of 63 respondents. This Analysis uses multiple linear regression analysis. The results showed that Work Stress and Work Environment influence Employee Performance.